LncRNA-MCM3AP-AS1 Promotes the Progression of Infantile Hemangiomas by Increasing miR-138-5p/HIF-1α Axis-Regulated Glycolysis - Mei, Haijun; Xian, Hua; Ke, Jing (Frontiers in Molecular Biosciences, 2021)
Infantile hemangioma (IH) is a common benign tumor of endothelial cells in infants. Most hemangiomas are self-limited, but a few may develop and lead to serious complications that affect the normal life of children. Therefore, finding an effective treatment strategy for IH is a pressing need. Recent studies have demonstrated that non-coding RNAs affect the progression of multiple tumors. This study aims to investigate the mechanism by which LncRNA-MCM3AP-AS1 promotes glycolysis in the pathogenesis of IH. We first documented that the expression of LncRNA MCM3AP-AS1 was significantly upregulated in IH. Furthermore, we demonstrated that MCM3AP-AS1 bound to miR-106b-3p which promotes glycolysis in IH. In addition, we found that inhibition of HIF-1α contributed to the transformation of glycolysis to normal aerobic oxidation, partially reversed the promoting effect on glycolysis by the up-regulation of LncRNA MCM3AP-AS1 in IH disease. More importantly, we demonstrated this phenomenon existed in IH patients. Taken together, we demonstrate that LncRNA-MCM3AP-AS1 promotes the progression of infantile hemangiomas by increasing the glycolysis via regulating miR-138-5p/HIF-1α axis.